2013
DOI: 10.3322/caac.21214
|View full text |Cite
|
Sign up to set email alerts
|

Silica: A lung carcinogen

Abstract: Silica has been known to cause silicosis for centuries, and evidence that silica causes lung cancer has accumulated over the last several decades. This article highlights 3 important developments in understanding the health effects of silica and preventing illness and death from silica exposure at work. First, recent epidemiologic studies have provided new information about silica and lung cancer. This includes detailed exposure-response data, thereby enabling the quantitative risk assessment needed for regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 10 publications
1
108
0
3
Order By: Relevance
“…Historically, this has been estimated to be in millions of people on an annual basis (US Department of Health and Human Services Progress Review, 2010; US Department of Labor, 2010; Steenland and Ward, 2014). Lung epithelial cells are constantly exposed to dust particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, this has been estimated to be in millions of people on an annual basis (US Department of Health and Human Services Progress Review, 2010; US Department of Labor, 2010; Steenland and Ward, 2014). Lung epithelial cells are constantly exposed to dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that chronic silicosis is most common in stone dressers, quarry workers, foundry workers, gold and black miners (Healy et al, 2014;Verma et al, 2011;Zhang et al, 2010;Ehrlich et al, 2011;Nelson et al, 2010). The Centers for Disease Control and Prevention (CDC) have recently reported that the incidence and mortality from silicosis are on a rise due to advanced mining techniques used to extract materials deeply embedded in quartz substrate and with increased efficiency that enriches the overall silica content in respirable dust exposure (Centers for Disease Control and Prevention (CDC), 2005; Steenland and Ward, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Silicosis may develop in some cases together with a variety of diseases including tuberculosis (Xia et al, 2014); CWP and autoimmune diseases (Maeda et al, 2010). Silica exposure is still prevalent in low and middle income countries, and developed countries also are not immune to new silica exposure (Steenland and Ward, 2014).…”
Section: Silicosismentioning
confidence: 99%
“…Crystalline silica is considered a potentially hazardous exposure to an estimated tens of millions workers worldwide 1. Respiratory exposures to crystalline silica result from drilling, mining and other activities that process silica-containing soil, sand, granite and other minerals in numerous industries.…”
Section: Introductionmentioning
confidence: 99%